Types of variables, descriptive statistics, and sample size - Feroze Kaliyadan; Vinay Kulkarni (Wolters Kluwer Medknow Publications, 2019)
This short "snippet" covers three important aspects related to statistics - the concept of variables, the importance, and practical aspects related to descriptive statistics and issues related to sampling - types of sampling and sample size estimation.